Optimal exercise temporal parameters of Traditional Chinese Exercises for cognitive function of older adults with mild cognitive impairment: a systematic review and dose–response meta-analysis of randomized controlled trials - Wen, Qingpan; Luo, Qin; Liu, Yangjun; Li, Lu; Białas, Marcin; Wilczyńska, Dominika (Frontiers in Medicine, 2025)
BackgroundMild cognitive impairment (MCI) is characterized by a progressive decline in memory and other cognitive functions, falling between normal cognition and dementia. Traditional Chinese Exercises (TCEs) have been proven effective for managing MCI. A dose–response meta-analysis was conducted to evaluate the correlation between exercise temporal parameters and their effectiveness in older adults with MCI.MethodsRandomized controlled trials (RCTs) on TCEs for MCI were searched across eight databases from their inception to September 2024. Literature was screened based on inclusion and exclusion criteria. Data from the selected studies were extracted, and the risk of bias was assessed using the RoB2 tool. The quality of the included studies was evaluated using the PEDro scale. The visualizations were conducted using the “robvis” package in R 4.3.3 software, while Stata 15.0 software was used to analyze the dose–response relations.ResultOut of 2,216 records,17 RCTs were included in the meta-analysis. Although significant heterogeneity was present among the studies, sensitivity analysis demonstrated good robustness. The results revealed significant improvements in cognitive function among older adults with MCI in the TCEs group: Montreal Cognitive Assessment (MoCA) (SMD = 1.04, 95% CI: 0.71–1.38) and Mini-Mental State Examination (MMSE) (SMD = 0.82, 95% CI: 0.41–1.42). The relations between exercise cycle, frequency, and overall cognitive function (MoCA and MMSE) followed a “Λ”-shaped curve. For MoCA, the relations with exercise duration also exhibited a “Λ”-shaped curve, while the relations between duration and MMSE was nonlinear. The peak improvements in MoCA and MMSE were observed at 12 weeks (25.59, 95% CI: 25.07–26.10) and 13 weeks (26.24, 95% CI: 25.38–27.09). Improvement was positively correlated with the number of cycles up to a peak, after which it declined, following a “Λ”-shaped pattern.ConclusionThis study demonstrates a nonlinear dose–response relations between exercise temporal parameters and therapeutic effects on cognitive function in older adults with MCI. Regarding exercise cycle, MoCA and MMES yield the optimal outcomes at 12 and 13 weeks. For exercise frequency, MoCA and MMES optimize results at three times per week. Concerning exercise duration, MoCA achieves optimal results at 45 min; MMES shows gradual improvement after 30 min.Systematic review registrationThe study protocol was registered with PROSPER on May 29, 2024, under the registration number CRD42024510378, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024510378